2014
DOI: 10.1175/jamc-d-13-071.1
|View full text |Cite
|
Sign up to set email alerts
|

A Trend Analysis of the 1930–2010 Extreme Heat Events in the Continental United States

Abstract: Extreme heat events (EHEs) are linked to mortality rates, making them an important research subject in both the climate and public health fields. This study evaluated linear trends in EHEs using the U.S. Historical Climatology Network (USHCN), version 2.0, dataset and quantified the longer-term EHE trends across the continental United States (CONUS). The USHCN-daily, version 1, dataset was integrated with the homogenized USHCN-monthly, version 2.0, dataset to create daily data for trend analysis. Time series a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 74 publications
7
29
0
Order By: Relevance
“…We make this distinction to acknowledge that underpinning drivers, climatology, seasonality, changes, and impacts of hot extremes depend heavily on event types (Barbier et al, 2018;Chen & Li, 2017;Freychet et al, 2017;Russo et al, 2017). For instance, the complex type, whose heat loads continue to mount rather than dissipate overnight, is reportedly far more damaging to human health (Meehl & Tebaldi, 2004;Oswald & Rood, 2014;Pezza et al, 2012). In particular, considering both the order of appearance for observations by Tmax-Tmin and severer human physiological responses (Nairn & Fawcett, 2015;Nicholls et al, 2008;Vaidyanathan et al, 2016), complex events are prescribed to take the form of hot day-night rather than the other way around.…”
Section: Methodsmentioning
confidence: 99%
“…We make this distinction to acknowledge that underpinning drivers, climatology, seasonality, changes, and impacts of hot extremes depend heavily on event types (Barbier et al, 2018;Chen & Li, 2017;Freychet et al, 2017;Russo et al, 2017). For instance, the complex type, whose heat loads continue to mount rather than dissipate overnight, is reportedly far more damaging to human health (Meehl & Tebaldi, 2004;Oswald & Rood, 2014;Pezza et al, 2012). In particular, considering both the order of appearance for observations by Tmax-Tmin and severer human physiological responses (Nairn & Fawcett, 2015;Nicholls et al, 2008;Vaidyanathan et al, 2016), complex events are prescribed to take the form of hot day-night rather than the other way around.…”
Section: Methodsmentioning
confidence: 99%
“…The above conclusions for changes in hot extremes are achieved based largely on univariate-based indices, such as hot days and annual maximum daily temperatures (Zhang et al, 2011). However, this univariate definitional framework, on the one hand, may introduce potential entanglements among types of hot extremes (Oswald & Rood, 2014;Oswald, 2018) and, on the other hand, tends to underestimate impacts exacerbated by coincident/interacted drivers (Fischer & Schär, 2010;Zscheischler et al, 2018). These flaws compromise the accuracy and consequently the utility of assessments of past changes, impacts, and future risks related to hot extremes.…”
Section: 1029/2019ef001202mentioning
confidence: 99%
“…However, this univariate definitional framework, on the one hand, may introduce potential entanglements among types of hot extremes (Oswald & Rood, 2014;Oswald, 2018) and, on the other hand, tends to underestimate impacts exacerbated by coincident/interacted drivers (Fischer & Schär, 2010;Zscheischler et al, 2018). Instead, a bivariate definitional framework, with the extremity of both daytime and nighttime temperatures constrained, is warranted to achieve a genuine nonoverlapping classification consisting of daytime-only, nighttime-only, and combined daytime-nighttime hot extremes (hereafter called combined hot extremes; Chen & Zhai, 2017;Gershunov et al, 2009;Mukherjee & Mishra, 2018;Oswald & Rood, 2014). A case in point is that a univariate constraint for hot days (daily maxima ≥90th percentile), which is intended for extreme daytime temperature only, may lead to an unintended identification of nighttime hot extremes as well, since the constraint fails to eliminate the possibility of threshold-exceeding nighttime minima.…”
Section: 1029/2019ef001202mentioning
confidence: 99%
“…Even though 2010 has high temperatures compared to previous years, a trend analysis of extreme heat events (EHE) from 1930 to 2010 showed that in 2010 there were more than 35 extreme minimum heat events (where temperatures are extremely low) over the southeastern US compared to about ∼ 10 events in 2006. In fact, the number of extreme minimum heat events is the highest overall for CONUS in 2010 compared to all the other years from 1930 onwards (Oswald and Rood, 2014). The Intergovernmental Panel for Climate Change (IPCC) reported that, since 1950, weather events have become more extreme likely due to climate change (IPCC, 2012).…”
Section: Differences In Chemical and Meteorological Icons/bconsmentioning
confidence: 99%